2017
DOI: 10.1099/ijsem.0.002191
|View full text |Cite
|
Sign up to set email alerts
|

Ramlibacter rhizophilus sp. nov., isolated from rhizosphere soil of national flower Mugunghwa from South Korea

Abstract: A Gram-negative, aerobic, non-motile, long rods or coccoid without flagellum strain, designated THG-YS3.2.7, was isolated from therhizosphere soil of a Mugunghwa flower collected from Kyung Hee University, Yongin, South Korea. Growth occurred at 10-40 °C (optimum 28-37 °C), at pH 6-8 (optimum 7) and at 0-5 % NaCl (optimum 1 %). The predominant ubiquinone was ubiquinone 8 (Q-8). The major cellular fatty acids were C10 : 0, C10 : 0 3OH, C16 : 0, C17 : 0, C17 : 0 cyclo, C18 : 0, C18 : 3ω6c (6,9,12), summed featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Ramlibacter tataouinensis TTB310 T (strain TTB310) is a beta-proteobacterium isolated from sand particles [55]. Different species from this genus were isolated in tropical forest soil [56] and the rhizospheric soil of Mugunghwa [57]. Furthermore, studies revealed that the genus of Ramlibacter has phosphatase activity [58] and ginsenoside-converting activity [59].…”
Section: Cassava/peanut Intercropping Changed the Microbial Communitymentioning
confidence: 99%
“…Ramlibacter tataouinensis TTB310 T (strain TTB310) is a beta-proteobacterium isolated from sand particles [55]. Different species from this genus were isolated in tropical forest soil [56] and the rhizospheric soil of Mugunghwa [57]. Furthermore, studies revealed that the genus of Ramlibacter has phosphatase activity [58] and ginsenoside-converting activity [59].…”
Section: Cassava/peanut Intercropping Changed the Microbial Communitymentioning
confidence: 99%
“…At the time of writing, only seven species had been described, based on the List of Prokaryotic names with Standing in Nomenclature (LPSN): Ramlibacter henchirensis , Ramlibacter tataouinensis , Ramlibacter solisilvae , Ramlibacter rhizophilus , Ramlibacter ginsenosidimutans , Ramlibacter monticola and Ramlibacter alkalitolerans . All of these seven species were isolated from different soil samples collected in forest [2, 3], rhizosphere [4], ginseng [5, 6] and subdesert [1]. The common characteristics of all species of the genus Ramlibacter are Gram-strain-negative and rod- or coccoid-shaped cells.…”
Section: Full-textmentioning
confidence: 99%
“…They contain ubquinone 8 (Q-8) as the major respiratory quinone and C 16 : 0 , summed feature 3 (C 16 : 1 ω 7 c and/or C 16 : 1 ω 6 c ) and summed feature 8 (C 18 : 1 ω 7 c and/or C 18 : 1 ω 6 c ) as the major fatty acid component. The DNA G+C content of members of this genus ranges from 66.6 to 69.9 mol% [1, 2, 4]. In this study, we report on the isolation and characterization of a novel bacterial species of the genus Ramlibacter , represented by strain MAH-25 T , isolated from soil sampled in a pine garden.…”
Section: Full-textmentioning
confidence: 99%
See 2 more Smart Citations